Potential for industrial production development in the Republic of Bashkortostan and in neighbouring regions - S. Sh. Aslaeva (Вестник университета)
Socio-economic development of regions depends on the level of interaction between them on the basis of their industry specialisation.   The purpose of the study is to determine the potential for the industrial production development of the regions for further activation of interregional interaction.   Types of industrial production of the Republic of Bashkortostan and its neighbouring regions are the object of the study.   The paper assesses its development in dynamics and statics by type of activity. Its specialisation is determined, the leading types of economic activity are identified with the use of localisation coefficients and localisation intensity. The development level of industrial production in the Russian Federation and in the regions near the Republic of Bashkortostan have similar trends, however, sharp fluctuations occur in Chelyabinsk and Sverdlovsk regions. In these subjects, the largest share in manufacturing belongs to metallurgical production. Also many activities that are to be in the zone of increased localisation in terms of the turnover of an organisation and the number of employees are actually in the zone of low effective localisation. Industrial production in the Udmurt Republic and the Republic of Tatarstan is less affected by the fluctuations. In Bashkortostan, the largest share is occupied by extraction of coke and petroleum products. To strengthen technological sovereignty, it is necessary to activate the interaction between regions in industrial production.